(untitled) (Journal of the College of Basic Education, 2026)
Wheat is a strategic crop in Iraq, a staple food for the population and a government priority to achieve self-sufficiency and enhance food security. Despite multiple efforts and programs, such as the Wheat Development Program that aims to increase productivity to address the lack of cultivated areas due to limited water, Iraq continues to rely on imports to fill the deficit in this vital crop.Accurate agricultural data is an important tool in measuring progress towards the SDGs and assessing the current state of agriculture. Farm land management is a critical macroeconomic component, as countries strive to achieve self-sufficiency and reduce dependence on imports, a key objective of economic and social development and the Sustainable Development Goals related to poverty eradication and responsible production and consumption. Increased productivity largely depends on plant health and physiological state.This research aims to clarify the concept of water stress and determine its impact on wheat production areas in Iraq and study vegetation cover based on a number of spectral indicators, through a comparative study between irrigated areas and demiah areas. Water stress in this context is defined as plant exposure to less than optimal amounts of environmental factors (such as water, climate, and nutrients), detrimental to its growth and development. The study will focus on the analysis of water stress resulting from various influencing factors in addition to the application of selected spectral indicators to represent the plant and plant health and water stress and it is known that the form of the relationship between the plant and its health and water stress take the form of the inverse relationship if the greater the health of the plant the less water stress.